Nucleobases in molecular recognition: molecular adducts of adenine and cytosine with COOH functional groups - Perumal, Sathiamurthi; Suresh, E.; Pedireddi, V. R. (Angewandte Chemie International Edition, 2005)
Keywords: carboxylic acids; hydrogen bonds; molecular recognition; nucleobases; supramolecular chemistry

Structural rationalisation of co-crystals formed between trithiocyanuric acid and molecules containing hydrogen bonding functionality - Ahn, Sung-Hoon; PrakashaReddy, J.; Kariuki, B. M.; Chatterjee, S.; Ranganathan, A.; Pedireddi, V. R.; Rao, C. N. R.; Harris, Kenneth D. M. (Chemistry - A European Journal, 2005)
Crystallisation of trithiocyanuric acid (TTCA) from various organic solvents that have hydrogen bonding capability (acetone, 2-butanone, dimethylformamide, dimethyl sulfoxide, methanol and acetonitrile) leads to the formation of co-crystals in which the solvent molecules are incorporated together with TTCA in the crystal structure. Structure determination by single-crystal X-ray diffraction reveals that these co-crystals can be classified into different groups depending upon the topological arrangement of the TTCA molecules in the crystal structure. Thus, three different types of single-tape arrangements of TTCA molecules and one type of double-tape arrangement of TTCA molecules are identified. In all co-crystals, hydrogen-bonding interactions are formed through the involvement of N-H bonds of TTCA molecules in these tapes and the other molecule in the co-crystal. Detailed rationalisation of the structural properties of these co-crystals is presented.
Keywords: crystal engineering; hydrogen bonds; nitrogen heterocycles; structure elucidation

Contrasting solid-state structures of trithiocyanuric acid and cyanuric acid - Guo, F.; Cheung, E. Y.; Harris, Kenneth D. M.; Pedireddi, V. R. (Crystal Growth & Design, 2006)
Although trithiocyanuric acid (TTCA) has been investigated widely as an agent in the formation of molecular cocrystals, the crystal structure of pure TTCA has never been determined. Attempts to grow crystals of pure TTCA by crystallization from solution invariably lead to the formation of solvate cocrystals, and desolvation of these materials leads to polycrystalline powder samples. In this paper, we report the structure determination of pure TTCA directly from powder X-ray diffraction data, using the direct-space genetic algorithm technique for structure solution followed by Rietveld refinement. The structure presents interesting contrasts to that of the oxygen analogue, cyanuric acid, and alludes to the possibility that both compounds might be capable of exhibiting polymorphism.

First study of metal hybrids of boronic acids: second-sphere coordination networks in the structures of 4-carboxyphenylboronic acid with some transition metals - Seethalekshmi, N.; Pedireddi, V. R. (Inorganic Chemistry, 2006)
Metal-organic hybrids of a boronic acid (4-carboxylphenylboronic acid) with Co(II), Mn(II), and Ni(II) salts have been reported for the first time. In all of the complexes, there is no interaction between the metal and boronic acid through dative bonds. Furthermore, second-sphere coordination, along with water clusters in the form of octamers, was observed in the absence of any other additional ligands. However, in the presence of aza-donor molecules such as 1, 2-bis(4-pyridyl) ethane, metal ions formed coordination polymers with those ligands, replacing the second-sphere coordination.

Molecules to supermolecules and self assembly: a study of some cocrystals of cyanuric acid - Marivel, S.; Suresh, E.; Pedireddi, V. R. (Tetrahedron Letters, 2008)
The preparation and structure elucidation of cocrystals 1a, 1b, 2a- 4a, formed from cyanuric acid (CA) and the aza-donor compounds 4,7-phenanthroline, 1,7-phenanthroline, phenazine and 1, 3 -bis(4-pyridyl) propane, respectively, have been reported. While CA forms different types of self-assembling modes-monomers (la), dimers (1b and 4a) and infinite tapes (2a and 3a)-the recognition of the constituents, however, is through a triple hydrogen-bonding pattern, consisting of an N-H center dot center dot center dot N and two C-H center dot center dot center dot O hydrogen bonds, except in 4a. (C) 2008 Elsevier Ltd. All rights reserved.

pK(a)-Directed host-guest assemblies: rational analysis of molecular adducts of 2,4-diamino-6-methyl-1,3,5-triazine with various aliphatic dicarboxylic acids - Delori, Amit; Suresh, Eringathodi; Pedireddi, V. R. (Chemistry-A European Journal, 2008)
Molecular adducts of 2,4-diamino-6-methyl-1,3,5-triazine (1) have been prepared with various aliphatic dicarboxylic acids. The molecular complexes (1a-1i) thus formed by co-crystallizing 1 with oxalic, malonic, succinic, fumaric, acetylene dicarboxylic, glutaric, thiodiglycolic, diglycolic, and adipic acids have been found to give two types of host-guest assemblies that have voids or channels in a three-dimensional arrangement. The different types of host-guest arrangement appear to result from differences in the acidity of the dicarboxylic acids, that is, acids with pK(a) < 3.0 give host networks that consist of 1 and the corresponding acid with water or solvent molecules of crystallization present as guests, whereas acids with pK(a) > 3.0 exist as guests in voids in a host network formed by 1. The former arrangement is observed in adducts 1a, 1b, 1c, and 1h and the latter arrangement is found in adducts 1c, 1d, 1f, 1g and 1i.
Keywords: dicarboxylic acids; host-guest systems; hydrogen bonds; molecular recognition; supramolecular chemistry

C-H center dot center dot center dot N hydrogen bonds mediated solid state structures of 2,2 `-bis (4-pyridylsulfanylmethyl)-1,1 `-biphenyl and 9-(4-pyridylsulfanyl)phenanthrene - Upadhye, Ketaki; PrakashaReddy, J.; Pedireddi, V. R. (Journal of Molecular Structure, 2009)
Solid state structure elucidation of sulfanyl ligands, 2,2'-bis(4-pyridylsulfany[methyl)-1,1'-biphenyl, L(1) and 9-(4-pyridylsulfanyl)plienanthrene, L(2) are reported. In the structures L(1) and L(2), the molecules are self-assembled through C-H center dot center dot center dot N hydrogen bonds, yielding ensembles of cyclic and helical networks. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: hydrogen bonds; noncovalent interactions; Supramolecular assemblies

Supramolecular synthesis of some molecular adducts of 4,4 `-bipyridine N,N `-dioxide - Arora, Kapildev K.; Talwelkar, Mayura S.; Pedireddi, V. R. (New Journal of Chemistry, 2009)
Molecular adducts (1a-1e) of 4,4'-bipyridine N,N'-dioxide, 1, respectively with cyanuric acid, trithiocyanuric acid, 1,3,5-trihydroxybenzene ( phloroglucinol), 1,3-dihydroxybenzene ( resorcinol) and 1,2,4,5-benzenetetracarboxylic acid have been reported. The major interactions observed in the structures 1a-1e are N-H center dot center dot center dot O, N-H center dot center dot center dot S, O-H center dot center dot center dot O and C-H center dot center dot center dot O, in the form of homomeric and heteromeric patterns of the constituents, either as a single or cyclic hydrogen-bonded motifs. While in the adduct 1a, both homomeric and heteromeric units of both the constituents were observed, no heteromeric interactions were observed in 1b and 1c. In addition, in 1b, homomeric aggregation of molecules of 1 occurred in association with water molecules. However, while heteromeric interactions prevail between the constituents in 1d and 1e, only one of the co-crystallizing species gave homomeric interactions (4,4'-bipyridine N,N'-dioxide in 1d; 1,2,4,5-benzenetetracarboxylic acid in 1e). Further, in either type of the patterns, the cyclic motifs are formed as a pair-wise hydrogen bonds comprising of strong and weak hydrogen bonds (N-H center dot center dot center dot O/C-H center dot center dot center dot O or O-H center dot center dot center dot O/C-H center dot center dot center dot O). In three-dimensions, the ensembles of molecules yield planar sheets, ladders and pseudorotaxane type assemblies.